Can the Large-Scale Decrement in Repetitive Nerve Stimulation Be Used as an Exclusion Criterion for Amyotrophic Lateral Sclerosis? - Shang, Li; Chu, Hong; Lu, Zuneng (Frontiers in Neurology, 2020)
Objective: To identify the characteristics of repetitive nerve stimulation (RNS) in patients with amyotrophic lateral sclerosis (ALS), and further verify the electrophysiological exclusion criteria of ALS. Methods: A total of 150 patients with ALS who were admitted to the Department of Neurology of Renmin Hospital of Wuhan University from January 2015 to December 2018 were enrolled. Clinical and electrophysiological data of enrolled patients were collected. The differences in the amplitudes of the compound muscle action potential (CMAP) between trapezius muscle (Trap) and abductor digiti minimi (ADM) in low-frequency RNS were compared. Furthermore, we analyzed the associations between decremental responses and gender, onset age, duration of disease, onset site, amyotrophic lateral sclerosis functional rating scale-revised (ALSFRS-r), disease progression rate, and CMAP amplitude. Results: Significant decrement (≥20% ) in at least one muscle was observed in 11.3% of the ALS patients. While decrements (≥10%) in at least one muscle was observed in 41.3% of the ALS patients. The decremental percentage in trapezius muscle was significantly higher than that in abductor digiti minimi (P <0.001); The onset age, duration of disease, onset site, and disease progression rate did not affect decremental responses. The decremental responses in RNS were more significant in ALS patients with low ALSFRS-R scores (p=0.01). Moreover, there was a positive linear correlation between the CMAP amplitude and the decremental percentage of Trap and ADM in ALS patients. Conclusions: CMAP decremental responses in RNS were common in ALS patients, suggesting abnormalities of neuromuscular junctions (NMJ). It is worthy of further discussion whether to consider decrement greater than 20% in RNS is a diagnostic exclusion criterion for ALS.